If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
3/9 = x/3 // - x/3
3/9-(x/3) = 0
1/3-1/3*x = 0 // - 1/3
-1/3*x = -1/3 // : -1/3
x = -1/3/(-1/3)
x = 1
x = 1
| 56-k=13 | | y+5-4yF=10 | | 2Y=8X-70 | | 18x-2(3x+5)=4(2x-8) | | 8w-4n=w | | -1/4(2-8) | | -2b+6=10 | | 4=2(3x-5)+15x | | -1/4(2y-8) | | 6/-3=7 | | 81/4-51/16 | | y=1/3x+b | | 2/3+1/2x+4+2x-1/3x-1/2 | | 1=0-x | | 4y=2X+7 | | 15x-38+2x-54=2(5x-3)+48 | | 3(1-2h)-6h=27 | | 7a-4a+5-8= | | f(-x)=2x^2+4x+8 | | 1/2(x+64)=14 | | -3t=60 | | x^4+3x^2-40= | | 13+6a+9a=4a+1 | | 2n^2-3n-6=0 | | (-6)-3b+8b+4= | | 8.25-5/16 | | 6r^2+17r-3=0 | | 5x^2+4=9x | | 9-4/v | | -3/2-2/3=-f/6 | | 34=2(1-8x)+8(6x-4) | | 11x-6=4(3x-1) |